Data from: Three-dimensional post-glacial expansion and diversification of an exploited oceanic fish - Shum, Peter; Pampoulie, Christophe; Kristinsson, Kristján; Mariani, Stefano (Zenodo, 2015)
Vertical divergence in marine organisms is being increasingly documented, yet much remains to be carried out to understand the role of depth in the context of phylogeographic reconstruction and the identification of management units. An ideal study system to address this issue is the beaked redfish, Sebastes mentella – one of four species of 'redfish' occurring in the North Atlantic – which is known for a widely distributed 'shallow-pelagic' oceanic type inhabiting waters between 250 and 550 m, and a more localized 'deep-pelagic' population dwelling between 550 and 800 m, in the oceanic habitat of the Irminger Sea. Here, we investigate the extent of population structure in relation to both depth and geographic spread of oceanic beaked redfish throughout most of its distribution range. By sequencing the mitochondrial control region of 261 redfish collected over a decadal interval, and combining 160 rhodopsin coding nuclear sequences and previously genotyped microsatellite data, we map the existence of two strongly divergent evolutionary lineages with significantly different distribution patterns and historical demography, and whose genetic variance is mostly explained by depth. Combined genetic data, analysed via independent approaches, are consistent with a Late Pleistocene lineage split, where segregation by depth probably resulted from the interplay of climatic and oceanographic processes with life history and behavioural traits. The ongoing process of diversification in North Atlantic S. mentella may serve as an 'hourglass' to understand speciation and adaptive radiation in Sebastes and in other marine taxa distributed across a depth gradient. Shum et al 3D usat genotypes Microsatellite data previously genotyped by Stefansson et al Heredity (2009) 102, 514–524. Dryad_mtDNA_Sebastes_Peter_Shum_Genbank_KP988027–KP988288 Mitochondrial control region of North Atlantic Sebastes (S. viviparus, S. fasciatus, S. norvegicus, S. mentella) Dryad_Rhodopsin_Sebastes_mentella_Peter_Shum_Genbank_KR818563–KR818700 ...